New susceptibility and resistance HLA-DP alleles to HBV-related diseases identified by a trans-ethnic association study in Asia. - Nao Nishida (Public Library of Science (PLoS), 2014)
Previous studies have revealed the association between SNPs located on human leukocyte antigen (HLA) class II genes, including HLA-DP and HLA-DQ, and chronic hepatitis B virus (HBV) infection, mainly in Asian populations. HLA-DP alleles or haplotypes associated with chronic HBV infection or disease progression have not been fully identified in Asian populations. We performed trans-ethnic association analyses of HLA-DPA1, HLA-DPB1 alleles and haplotypes with hepatitis B virus infection and disease progression among Asian populations comprising Japanese, Korean, Hong Kong, and Thai subjects. To assess the association between HLA-DP and chronic HBV infection and disease progression, we conducted high-resolution (4-digit) HLA-DPA1 and HLA-DPB1 genotyping in a total of 3,167 samples, including HBV patients, HBV-resolved individuals and healthy controls. Trans-ethnic association analyses among Asian populations identified a new risk allele HLA-DPB1*09 ∶ 01 (P = 1.36 × 10(-6); OR= 1.97; 95% CI, 1.50-2.59) and a new protective allele DPB1*02 ∶ 01 (P = 5.22 × 10(-6); OR = 0.68; 95% CI, 0.58-0.81) to chronic HBV infection, in addition to the previously reported alleles. Moreover, DPB1*02 ∶ 01 was also associated with a decreased risk of disease progression in chronic HBV patients among Asian populations (P = 1.55 × 10(-7); OR = 0.50; 95% CI, 0.39-0.65). Trans-ethnic association analyses identified Asian-specific associations of HLA-DP alleles and haplotypes with HBV infection or disease progression. The present findings will serve as a base for future functional studies of HLA-DP molecules in order to understand the pathogenesis of HBV infection and the development of hepatocellular carcinoma.